Digital Transformation of Additional Professional Education: Features of the LK-14 Educational Platform - Alekseeva, Galina I. (2020)
This article substantiates the relevance of the transformation of the educational environment of additional professional education (APE) in the Republic of Sakha (Yakutia). This study aims to justify the transformation of the educational environment of APE in the context of digitalization and to consider the prospects for targeted professional development of teachers in the republic according to their needs. The authors chose this scientific topic due to the pressing needs of Russian continuing professional education (CPE) and current problems such as the lack of unified approaches and mechanisms for regulating the professional development of teachers in the digital educational environment and the lack of methods for monitoring the effectiveness and efficiency of CPE distance learning programs. Creating an innovative and dynamic CPE system requires the intensive introduction of information technologies into education. These technologies ensure that the learning process is open and of high quality, as well as provide access to global educational resources. This helps learners create “their own individual educational environment” reflecting their needs and requirements. The research methods used to explore this problem were a pedagogical experiment, the analysis of the organization of CPE of teachers in the region, designing a regional model of targeted personalized training of educators and administration. The research results include the specifics of APE modernization in the region and the model of targeted personalized training of teachers of the republic. The qualitative novelty of this model stems from the fact that developing teachers’ competencies involves identifying gaps in their professional knowledge and building individual learning paths.